INOVASI MEDIA PEMBELAJARAN BAHASA ARAB BERBASIS E-LEARNING - Silahuddin silahuddin; Azhari Azhari (PTE FTK UIN Ar-Raniry, 2019)
The Arabic teaching-learning proccess at the Madrasah Aliyah in Aceh Besar has not been running optimally. Generally, the learning process is still conventional based. Therefore, a solute efforts is needed for a teacher to design and create learning medias based ICT. Namely: computer-based media, websites, online library, e Learning and android that can facilitate the spread of knowledge. This research are to investigate how the utilization of ICT can be used optimally in learning and how the ability of teachers in using ICT facilities as a learning media innovation. The research used is a research development with mixed method methodology, and the sample of the research is Madrasah Aliyah teachers in Aceh Besar District. The results showed: generally, the teachers have already known and understood the use of media in learning. Nevertheless, Teachers rarely most of them do not use e learning. The teachers have not done the innovation of learning media of ICT based. The researcher recommends. The Medias e learning can be used optimally in learning Arabic at Madrasah Aliyah Aceh Besar District.